2016
DOI: 10.1200/jco.2015.65.6603
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Risk of Cardiovascular Events in Women With Nonmetastatic Breast Cancer

Abstract: Purpose Cardiovascular disease (CVD) is a leading cause of death among women with nonmetastatic breast cancer. Whether exercise is associated with reductions in CVD risk in patients with breast cancer with an elevated CVD risk phenotype is not known. MethodsUsing a prospective design, women (n = 2,973; mean age, 57 years) diagnosed with nonmetastatic breast cancer participating in two registry-based, regional cohort studies, completed a questionnaire that assessed leisure-time recreational physical activity (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(102 citation statements)
references
References 43 publications
3
93
0
6
Order By: Relevance
“…Among breast cancer survivors, a reduction in physical activity levels following diagnosis and treatment is common . Importantly, physical activity following a cancer diagnosis is associated with a 38% reduction in breast cancer‐specific mortality and an incremental reduction of cardiovascular events in breast cancer survivors . Therefore, the success of NExT in increasing physical activity levels and maintaining this increase for a period of 2 years after initiating adjuvant treatment has the potential to influence important clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Among breast cancer survivors, a reduction in physical activity levels following diagnosis and treatment is common . Importantly, physical activity following a cancer diagnosis is associated with a 38% reduction in breast cancer‐specific mortality and an incremental reduction of cardiovascular events in breast cancer survivors . Therefore, the success of NExT in increasing physical activity levels and maintaining this increase for a period of 2 years after initiating adjuvant treatment has the potential to influence important clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study with non-metastatic breast cancer patients showed that exercise is associated with a reduction in the incidence of cardiovascular events [43]. Runowicz et al [10] recommend among other things early cardiovascular monitoring and education of breast cancer survivors about lifestyle adaptations including exercise.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…[18] A prior study in our cohorts found greater physical activity was associated with lower CVD risk in a dose-response fashion, independent of BMI at diagnosis. [19] Physical activity interventions among breast cancer survivors could be a promising area for CVD prevention: to date no controlled study has had sufficient follow-up or sample size to demonstrate effects on CVD morbidity/mortality, though many have demonstrated safety/efficacy for treatment-related side effects, quality of life, resting heart rate and blood pressure. [2022]…”
Section: Discussionmentioning
confidence: 99%
“…Participants were drawn from a well-characterized population of Kaiser Permanente Northern California (KPNC) health plan members enrolled in two prospective cohorts with similar characteristics: LACE [19]) and Pathways [20]. The 2,135 LACE participants were diagnosed with breast cancer (AJCC stage I-IIIA) from 1997–2000 and were 18–79 years old.…”
Section: Methodsmentioning
confidence: 99%